THE SIGNIFICANCE OF VALUE TRANSFER TO CHILDREN - Raşit KOÇ (Fırat University, 2019)
Contemporary individuals experience their lives by utilizing several utilities provided by technological innovations and scientific advances. Almost every day, a new innovation or invention is introduced. All these developments, innovations, and advances in the field of information and technology facilitate the lives of individuals, however also introduce certain problems and decay in values in private lives. One of such problems is the adoption of a self-centered, individual lifestyle via introversion and isolation from the society. Our children open their eyes to a life that only includes what modern life provides without an awareness about their cultural heritage, and they consider that the life only includes the life in the virtual world. This approach and the rapid changes in lifestyles forced families, educators, and all those interested in social affairs to attempt to transfer the values, which are the cornerstones of the culture and belief system, to future generations. In this context, in recent years, "education of values" became an important topic in the field of education both globally and in Turkey. It became inevitable to include own values and universal values while restructuring the educational programs. The present study focused on the importance of transferring values, which are a significant element in social life, to children and the contribution of values to the development of the personality and identity of the children.